INVESTIGATING CONSUMER AWARENESS AND ATTITUDES TOWARDS ECO-FRIENDLY PRODUCTS - V. Usha; Kumar, P. Ashok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study delves into the increasing consumer awareness and demand for eco-friendly products in light of growing environmental concerns. Various media outlets highlight issues such as climate change and pollution, driving consumers to inquire about a product’s environmental footprint throughout its life cycle. Businesses recognize the competitive advantage of eco-friendly products, leading to innovation in sustainable offerings. A comprehensive review of literature and data analysis reveals key factors influencing consumer attitudes and behaviors towards eco-friendly products. Product quality, social responsibility, health benefits, and prestigious branding significantly shape consumer preferences, while demographic factors like age, education, and income also play crucial roles. The study’s findings underscore the importance of educational campaigns, increased product availability, and transparency in labeling to promote eco-friendly consumption. It suggests fostering collaborations among businesses, policymakers, and environmental organizations to drive sustainable practices. Future research should explore deeper psychological and socio-economic factors influencing consumer behavior and assess the effectiveness of policy interventions and corporate sustainability initiatives. The implications extend to businesses, policymakers, environmental organizations, and consumers, encouraging informed choices that align with sustainability goals. By leveraging insights into consumer attitudes, stakeholders can collectively foster a culture of sustainability and drive positive environmental change. This study provides valuable recommendations for promoting eco-friendly products and highlights the potential for further research to advance environmental conservation efforts. Ultimately, understanding consumer attitudes towards eco-friendly products empowers individuals and organizations to make decisions that contribute to a healthier and more sustainable future for the planet.